(untitled) (Research, Society and Development, 2021)
Yards characterize land use options able to reconcile agricultural and forestry production, simultaneously with the conservation of natural resources. This study aimed to characterize and identify plant species with medicinal potential in 44 yards, cultivated and managed by family farmers, in rural communities in Alta Floresta (AF) and Nova Canaã do Norte (NCN), Portal da Amazônia (MT). Guided visits were made in the yards, during the month of August 2017, to map and identify the present species. We identified 151 species with medicinal potential (76 species in both municipalities, 38 exclusively in AF and 37 in NCN, 38% exotic and 62% native), belonging to 59 botanical families (notably Asteraceae, Lamiaceae, Fabaceae and Euphorbiaceae). The species are distributed in three strata, characterizing an agroforestry consortium (42% are herbaceous, 25% arboreal, 23% shrubby, 8% lianas and vines and 1% epiphytes). The results point to a wide distribution of species and diversification in yards, in different communities, with no relationship between the age/size of yards and species richness. The choice of species by farmers does not follow a pattern, that is, most do not choose the same species for cultivation, and the distribution of these species in all strata (tree, shrub and herbaceous) in the yards, indicates their potential for the construction of agroforestry consortia. The high number of medicinal species in the upper stratum - of arboreal size - stands out, which is important for the reinsertion of trees in properties, communities, and in the landscape of Portal, characterized by deforestation.